Optimization of CO2 Laser Cutting Variables of Sengon Plywood (Paraserianthes falcataria) Using Response Surface Methodology - Nugraha, Muhammad Dimaz; Iswandaru, Dian; Duryat; Hidayat, Wahyu (Journal of Sylva Indonesiana, 2024)
Sengon (Paraserianthes falcataria) wood is used for various purposes, including furniture, plywood, pallets, and building materials. Consumer demand for decorative wood is increasing, so innovation is needed to make it more productive and efficient. A laser cutting machine is one of the alternatives to answer this problem. Because CO2 gas wavelength and energy density offer the highest cutting quality, CO2 lasers are appropriate for wood processing. This study aims to determine the effect of laser power intensity and cutting speed on cutting plywood to get the best results. The plywood used has a thickness of 12 mm. The laser intensities used were 30 Watt, 35 Watt, 40 Watt, 45 Watt, and 50 Watt with cutting speeds of 2 mm/s, 4 mm/s, 6 mm/s, and 8 mm/s, with nozzle standoff distance set to 10 mm. In each repetition on the same sheet determine the comparison or variation of each variable used. Based on the measurement results, the highest width was obtained at 50 Watt power and 2 mm/s speed, and the lowest at 35 Watt power and 8 mm/s. The highest depth was 50 Watt and 2 mm/s, and the lowest was 30 Watts and 4 mm/s. The overall color change (âˆ†E*) increased with increasing laser power. The higher the laser power, the more the color change increases. The change in âˆ†E* decreased as the laser speed increased. The optimization of cutting sengon plywood with CO2 laser using RSM method resulted in an optimum combination at 40 Watt laser power and 8 mm/s speed with a desirability value of 0.623